2012
DOI: 10.3892/ol.2012.887
|View full text |Cite
|
Sign up to set email alerts
|

Dermatofibrosarcoma protuberans: Our experience of 59 cases

Abstract: Abstract. Dermatofibrosarcoma protuberans (DFSP) is a rare soft tissue tumor with intermediate malignancy. It is initially located on the skin from where it is able to infiltrate the deep structures and has a tendency to recur locally following inadequate excision. A t(17;22)(q22;q13) chromosome translocation is the main cytogenetic alteration responsible for the onset of DFSP. Treatment options include complete surgical excision by performing conventional surgery with wide margins (>3 cm) or Mohs micrographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 41 publications
2
37
1
1
Order By: Relevance
“…Certain studies have advocated the use of Mohs micrographic surgery with incremental excision until normal tissue is obtained, as documented by repeat frozen sections (13). Several studies have demonstrated a significant correlation between a wide excision and a low recurrence rate (9,13). In the present study, the recurrence of DFSP occurred in 26 cases (38.2%).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Certain studies have advocated the use of Mohs micrographic surgery with incremental excision until normal tissue is obtained, as documented by repeat frozen sections (13). Several studies have demonstrated a significant correlation between a wide excision and a low recurrence rate (9,13). In the present study, the recurrence of DFSP occurred in 26 cases (38.2%).…”
Section: Discussionmentioning
confidence: 49%
“…However, CD34 immunohistochemical positivity is also expressed by other spindle cell tumors, including solitary fibrous tumors, sclerotic fibroma, superficial acral fibromyxoma, cellular digital fibroma, dermatofibroma and nuchal-type fibroma. Additional immunohistochemical staining of factor XIIIa, stromelysin III, CD44, CD163 and D2-40 have been found to be positive in dermatofibroma and negative in DFSP (1)(2)(3)(4)(6)(7)(8)(9)(10). Spindle tumor cells are immunonegative for S100 protein, smooth muscle actin, desmin, cytokeratin and epithelial membrane antigen (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…1,[9][10][11] Median age at diagnosis is 20-59 years 1 ; however, congenital and paediatric cases have also been described. 2,[12][13][14][15][16] As for all soft tissue sarcomas, DFSP has no specific risk factors; it arises generally on healthy skin but occasionally can develop on chronically damaged areas. 5,16 Despite its rapid progression during pregnancy, it is not demonstrated an eventually hormonal origin.…”
Section: Introductionmentioning
confidence: 99%
“…2,[12][13][14][15][16] As for all soft tissue sarcomas, DFSP has no specific risk factors; it arises generally on healthy skin but occasionally can develop on chronically damaged areas. 5,16 Despite its rapid progression during pregnancy, it is not demonstrated an eventually hormonal origin. 17 The malignant potential of DFSP is considered as intermediate between that of dermatofibroma and malignant fibrous histiocytoma.…”
Section: Introductionmentioning
confidence: 99%
“…Dentro de las técnicas quirúrgicas disponibles están la exéresis simple, la exéresis amplia y la cirugía micrográfica de Mohs, aunque existe cierta controversia entre estas 2 últimas. En la actualidad, independientemente de la téc-nica que se elija, se recomiendan unos márgenes libres de resección de 2-3 cm más allá de los límites macroscópicos visibles del tumor, a veces incluyendo la fascia muscular subyacente [13][14][15] . A pesar de las escisiones locales amplias, todavía se observan tasas de recurrencia local próximas al 20 % 10 .…”
Section: Dermatofibrosarcoma Protuberansunclassified